PERANAN BAHASA INGGRIS DI BIDANGINDUSTRI PARIWISATA DI TOBELO - Galela, Dolfina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT DOLFINA GALELA. The Role of English Language In the Tourism Industry at Tobelo. (Supervised by Drs. Fentje Kodong, MA, Arter J. Senduk, SS, M. Hum). Tourism sector has a good prospect in the future, because it can  give big foreign exchange for developing tourism sector. Developing tourism sector needs several factors of human resources, one of them is the communications factors in which language as a means of verbal communication plays an important role. The functions of language and such ast o develop  science and technology. And to communicate with other country. The people who are involved in the tourism industry are required to communicate with the tourists in their language. The language which is often used to communicate with the foreign tourist is English. If they cannot understand the English language, the foreign tourist will often find difficulties in communication. The problem are :What are the roles of English tourism in Tobelo? The hypothesis is that the role of the English language and the ability of a person in using the English language is important in the tourism industry. The objectives of this investigation are to undserstand The Role of English Language In the Tourism Industry at Tobelo ; to understand to ability of the English language of a person in tourism industry so far; to understand the hindrances in the tourism industry in using the English language, the writer uses the tabulation method to analyse the data into the table form and to interpret the table. Based on the investigation result, according to the informants that the role of the English language is important to support the communication and their services to the foreign tourists. According to the tourists, the ability of the English language of a person in the tourism industry is enough.  The persons who includes in the tourism industry has the hindrances in using the English language, for example, the speed of speaking, pronunciation of tourists. They used several ways to handle these hindrances, such as they used to interrupt if they do not understand about the meaning, they use dictionary and gestures to handle these hindrances.   -------------------------------------------------------------------------------------------------------------- Keywords : Role, English, Tourism, Tobelo, Industry